2022
DOI: 10.3389/fpsyg.2022.746192
|View full text |Cite
|
Sign up to set email alerts
|

Altered Processing of Social Emotions in Individuals With Autistic Traits

Abstract: Social impairment is a defining phenotypic feature of autism. The present study investigated whether individuals with autistic traits exhibit altered perceptions of social emotions. Two groups of participants (High-AQ and Low-AQ) were recruited based on their scores on the autism-spectrum quotient (AQ). Their behavioral responses and event-related potentials (ERPs) elicited by social and non-social stimuli with positive, negative, and neutral emotional valence were compared in two experiments. In Experiment 1,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Because these traits did not correlate with vocal emotion perception in the present study, they are unlikely to explain the benefit of musicality. Nevertheless, the differential link between musicality and autistic traits seems worth exploring in more detail, as other studies reported relationships between autistic traits and voice identity perception (Skuk et al., 2019) as well as emotional processing (Yang et al., 2022). While not differing on the total AQ score, musicians seem to score lower on the social communication domain, but higher on the attention to detail domain, when compared with non‐musicians.…”
Section: Discussionmentioning
confidence: 99%
“…Because these traits did not correlate with vocal emotion perception in the present study, they are unlikely to explain the benefit of musicality. Nevertheless, the differential link between musicality and autistic traits seems worth exploring in more detail, as other studies reported relationships between autistic traits and voice identity perception (Skuk et al., 2019) as well as emotional processing (Yang et al., 2022). While not differing on the total AQ score, musicians seem to score lower on the social communication domain, but higher on the attention to detail domain, when compared with non‐musicians.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, individuals with high scores on the AQ questionnaire were considered to have autistic traits ( 26 , 28 , 29 , 54 , 55 ) and it was used to select participants in the present study. The P2 amplitudes in the High-AQ group were larger than those in the Low-AQ group when they viewed painful static stimuli, while the P2 amplitudes of the two groups did not differ in response to painful dynamic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The EPSS-Face database contains 160 digital pictures of faces in painful or non-painful situations. Some of the stimuli have been used in previously published studies (Li et al, 2020 ; Meng et al, 2020a ; Yang et al, 2022 ). These stimuli were revised from a picture database that had been previously validated, in which the images of the faces were morphed pictures with given black backgrounds and shown in grayscale (Hu et al, 2018 ; Yang et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%